Foreword. ‘Managing the Triple Helix’: Regions as Place-Based and Industry-Based Political Arenas - Emanuela TODEVA; Panagiotis KETIKIDIS (Management Dynamics in the Knowledge Economy, 2017)
Research at the intersection of industries, regions, cities, clusters and economic growth has populated the academic literature with new concepts such as placed-based policies and strategies. Place-based policy initiatives started with social policies that are trying to address issues of poverty, community development, or social services, enabling local actors to participate in policy development processes and to take greater control of their own destinies. Place-based policies usually evolve specific policy experiments which involve innovation and learning across multiple levels of government (Bradford, 2008)...